Participação de receptores muscarínicos e da via do óxido nítrico no efeito espasmolítico da fração de alcalóides totais obtida de Solanum paludosum Moric: (Solanaceae) - Monteiro, Fábio de Souza (2009)
Solanum paludosum Moric. (Solanaceae) is an herbaceous species, known popularly as "jurubeba-roxa" in the Northeast of Brazil (AGRA; BHATTACHARYYA, 1999). The chemical and pharmacological studies with root bark of this species showed the presence of glycoalkaloids, and that the ethanol extract and aqueous phase obtained the same parts showed spasmolytic activity (ATAÍDE, 1982; BARBOSA-FILHO et al., 1991; BASÍLIO, 2008). As glycoalkaloids are known to present cytotoxicity and many species of Solanum present spasmolytic activity, decided to study the total alkaloids fraction from root bark of S. paludosum (FAT-SP) on the cytotoxic potential in rat s erythrocytes and to investigate the spasmolytic activity in rat uterus, rat aorta and guinea-pig ileum and trachea. FAT-SP did not show hemolytic activity but presented non-selective spasmolytic effect. The preliminary pharmacological screening showed that FAT-SP on rat uterus, did not inhibit the oxytocin (10-2 IU/mL)-induced phasic contractions, but significantly inhibited the CCh (10-5 M)-induced phasic contractions (IC50 = 178.8 ± 7.1 μg/mL). On guinea-pig trachea, was about 2.2 times more potent in relax the trachea pre-contracted with CCh 10-6 M in the absence (EC50 = 159.4 ± 23.0 μg/mL) than in the presence (EC50 = 353.2 ±15.2 μg/mL) of functional epithelium; on guinea-pig ileum, inhibited the CCh (10-6 M)-induced phasic contractions (IC50 = 129.8 ± 3.7 μg/mL) and was more potent in relation to histamine (10-6 M)-induced contractions (Emax = 18.4 ± 2.3%) and on rat aorta, we observed that FAT-SP relaxes the rat aorta pre-contracted with phenylephrine 3 x 10-7 M of manner more potent in the presence (EC50 = 75.4 ± 6.2 μg/mL) than absence (EC50 = 242.8 ± 11.7 g/mL) of functional endothelium. According with the parameter of potency FAT-SP was more potent on guinea-pig ileum and rat aorta. Thus, we decided to investigate a possible mechanism of action in these organs. FAT-SP relaxed in a significant and concentration dependent manner the guinea-pig ileum pre-contracted with 10-6 M CCh (EC50 = 37.4 ± 3.2 μg/mL) or histamine (EC50 = 54.2 ± 2.9 μg/mL), but not with 40 mM KCl (Emax = 28.6 ± 2.8%). Since, FAT-SP was more potent to relax the ileum pre-contracted with carbachol, this is suggestive the involvement of muscarinic receptors in this effect. This hypothesis was confirmed in functional level by the observation that the FAT-SP shifted to the right the cumulative concentration-response curves to CCh without changing the Emax, which is characteristic of competitive antagonism to the CCh. The relaxation produced by FAT-SP on rat aorta in the presence of L-NAME 10-5 M (EC50 = 147.0 ± 22.1 g/mL), the NO synthase inhibitor, was attenuated, but not in the presence of atropine 10-6 M (EC50 = 93.3 ± 10.0 g/mL), a non-selective muscarinic receptor antagonist, or indomethacin 10-5 M (EC50 = 90.7 ± 13.2 g/mL), a non-selective COX inhibitor, thus suggesting the involvement of the endothelial NO synthase. Furthermore, in the presence of hydroxocobalamin 3 x 10-5 M (EC50 = 294.9 ± 20.4 μg/mL), a scavenger of NO, or ODQ 10-5 M (EC50 = 228.2 ± 30.9 μg/mL), a selective blocker of soluble GC, the relaxation curve of FAT-SP was attenuated, suggesting the involvement NO/CG pathway in the spasmolytic effect of the FAT-SP.